ANALISIS USAHATANI KELAPA SAWIT YANG MENGGUNAKAN KOMBINASI PUPUK ORGANIK DAN ANORGANIK DI KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Angga Tusdiansyah (Universitas Pasir Pengaraian, 2020)
This study aims to 1) Calculate the productivity of oil palm plantations that use a combination of organic and inorganic fertilizers in Kerumutan District, Pelalawan Regency, 2) Analyze the income of farming oil palm plantations that use a combination of organic and inorganic fertilizers in Kerumutan District, Pelalawan Regency. The study was conducted in Kerumutan Village and in Banjar Panjang Village, Pelalawan Regency, Riau Province. The research method used was a survey method, and samples were taken by purposive sampling technique. Samples are oil palm farmers who have provided a combination of organic and inorganic fertilizers in their oil palm plantations for at least 2 years, and have a production record for 1 year. Analysis of the data used is quantitative descriptive analysis and farm analysis. The results showed that the productivity of oil palm plants using a combination of organic and inorganic fertilizers in Kerumutan District, Pelalawan Regency was 23,431.47 tons / ha / year with an average plant age of 16 years. Net income received by respondent farmers is Rp. 16,307,921.57 / ha / year with a Return Cost Ratio (R / C) of 1.94.